Pain and Suffering: The Reality of Being Positive with HIV/AIDS - Retno Lestari; Wenny Nugrahati Carsita (International Journal of Public Health Science (IJPHS), 2016)
HIV/AIDS remains a global health problem and affects the overall quality of life. People living with HIV/AIDS are at risk for developing mental health problems, such as depression and anxiety. This condition can fuel additional problems, such as non-compliance in taking HIV medications. This study aimed to explore the meaning in life while living with HIV/AIDS among people in West Java.This study used an interpretive phenomenological approach. Data were collected by in-depth interviews among 7 participants who experienced HIV-positive. The results were analyzed by Van Manen method. Four themes were identified in this study: (1) experiencing mental suffering, (2) be free from mental suffering, (3) trust the HIV/AIDS disease is not contagious and there is a hope to liveand (4) performing activities to improve the quality of life. Participantsfeels that living with HIV/AIDS is not easy. They suffered from fear and anxiety, on the other hand it emerged as a hope and decision to seek support, treatment, and performing activities to improve the quality of life.